Oxyresveratrol and trans-dihydromorin from the twigs of Cudrania tricuspidata as hypopigmenting agents against melanogenesis. (March 2015) - Hu, Shuting; Zheng, Zongping; Zhang, Xinchen; Chen, Feng; Wang, Mingfu
Highlights: Both oxyresveratrol and trans- dihydromorin are potent skin lightening agents. The depigmenting mechanism of oxyresveratrol and trans- dihydromorin are different. Trans- dihydromorin is more effective in 3-dimensional artificial skin model. Abstract: The depigmenting effects of oxyresveratrol and trans- dihydromorin were investigated in b16F10 cell line and its synergetic melan-a cells, as well as in 3-dimensional skin models. But their inhibitory effects were different in two cell lines. In b16 cells, oxyresveratrol showed stronger depigmenting effect than trans- dihydromorin, with greater suppression on tyrosinase activity. Both of them induced post-transcriptional degradations of microphthalmia-associated transcription factor (MITF), leading to significant decreases of tyrosinase related protein 1 (TRP-1) and tyrosinase related protein 2 (TRP-2) production. In melan-a cells, trans- dihydromorin exhibited stronger inhibition on melanin synthesis. It also induced greater suppression on the levels of tyrosinase, TRP-1 and TRP-2 via MITF down-regulation at both transcription and translation level. Evaluations in artificial skin model also demonstrated the depigmenting effects of trans- dihydromorin. In conclusion, we found that trans -dihydromorin is an effective hypopigmenting agent in normal skin cells. Furthermore we demonstrated that hypopigmenting agents effective in melanoma system may not be effective on normal melanocytes, indicating that a non-tumor melanocyte system is more suitable for the screening of hypopigmenting agents.